Criteria for the normativity of interpretative legal acts in Russian judicial practice - E. V. Timoshina; A. A. Kraevsky (Правоприменение)
The subject. The article focuses on the concept of acts which clarify legislation and have normative properties (acts with normative properties, or ANPs). This concept was introduced in Russia’s procedural legislation in 2016 in order to allow such acts to be challenged by way of judicial review. ANPs are different from normative acts and, in accordance with the established doctrinal classification, can be described as interpretational acts.The purpose of the article is to examine the nature of ANPs and the way in which Russia’s courts decide judicial review claims which seek to challenge ANPs.The methodology includes interpretation of Russian procedural legislation and analysis of doctrinal researches on judicial review of ANP. The authors also analyze the materials of the empiric monitoring of judgments in ANP judicial review cases and ascertain the criteria of normativity which are relied upon by Russia’s courts when identifying ANPs and distinguishing between ANPs and other legal acts – primarily, between ANPs and normative acts. The main results, scope of application. The authors describe the drafting defects in the procedural legislation and maintain that the statutory definition of ANP lacks clarity. The authors put forward their own definition of ANP as distinguished from normative acts, on the one hand, and acts that apply legal norms, on the other hand. The authors argue that, in contrast to normative acts, ANPs not only lay down the will of the issuing authority, but also have a knowledge acquisition (cognitive inquiry) component in them. There is a logical and semantic link between the content of an ANP and the norms which are contained in a normative act and are interpreted by the ANP. In contrast to an act of legal application, the validity of an ANP depends not only on the competence of the authority that issued the ANP, but also on the validity of the normative act interpreted by the ANP. Further, acts of legal application, but not ANPs, establish a logical correspondence between individual objects and the general concepts used in legal norms.The authors also analyze the doctrinal works on judicial review of ANP. The scholars who criticize the introduction of this procedure in the legislation believe the concept of ANP to be superfluous for various reasons and argue that ANPs are either non-normative acts or defective normative acts. The authors of this article, however, maintain that the scholars who criticize the concept of ANP do not take into account the special nature of ANP normativity – i.e., normativity of interpretational acts. The authors put forward a hypothesis regarding the way in which courts are likely to treat ANP judicial review cases, describe the materials of the empiric monitoring, and then provide the statistical result of the said monitoring.Conclusions. The analysis of the content of judicial acts allowed the authors to identify five types of interpretational collisions between the original legislative norm and its interpretation (clarification) in an ANP. The reasoning of the courts was analyzed to reconstruct the criteria used by the courts to establish whether a challenged legal act has normative properties. The authors identified that the courts consider that there are two ways in which an ANP can acquire normative properties: either through the expression of the will of the issuing authority or through actual application of an ANP. The authors describe the criteria of both types of ANP.The authors conclude the article with the description of the main problems revealed during the monitoring and propose their possible solutions.